Socio-Economic Challenges and Proposed Solutions to Address the Fragmentation of Agricultural Land Holdings in Egypt (London Journal of Research In Humanities and Social Sciences, 2024)
Agriculture land in Egypt is paramount to the nation’s economy, food security, and social fabric. Egypt’s rich history of agriculture, dating back to ancient civilizations along the Nile, has shaped the country’s identity and sustenance for millennia. Agriculture has been the lifeblood of Egypt for thousands of years, with the fertile Nile Delta and Nile Valley serving as the cradle of Egyptian civilization. The annual inundation of the Nile River, combined with innovative irrigation techniques developed over centuries, has allowed Egypt to sustain a thriving agricultural sector. Today, agricultural land in Egypt remains a cornerstone of the nation’s economy, providing food, raw materials, and employment for millions. Small land holdings play a pivotal role in Egypt’s agricultural landscape. These holdings are typically characterized by limited acreage, often less than two hectares, and are predominantly managed by individual families. Small-scale family farms form the ackbone of Egypt’s agricultural sector, contributing significantly to crop production, livestock rearing, and the livelihoods of rural communities (Muhammad,2018). Fragmented land ndicates that it is divided among many legal heirs as it passes from one generation to another. Moreover, non-conducive government policies also lead to such fragmentation. It severely affects agriculture as the mechanization cannot be carried out on small fragmented and. Due to this numerous adverse challenges are to be expected besides the direct loss of gricultural land due to urban settlements expansion and road network construction. Such effects are caused mainly due to the mechanisms of fragmentation; and division of large patches of agricultural land into smaller and smaller patches. This leads to Smaller land patches, which means higher agricultural costs and the inability to use new agricultural techniques that favor larger patches, added to the increased water requirements, loss of biodiversity, soil erosion, and fertilizer leaching Plus the emissions from the urban settlements and the continuous traffic on the road networks, which lead to contamination of the soil and plants surrounding them (Mahmoud,2014).
Keywords: Modeling.; techniques; javelin throwing; individualization; ideology; Violence; Values; axiology; drama; manipulation; totalitarianism; superman; Mother child relations. Parent child relations. Premature birth.; Egypt; Fragmentation; Agricultural land holding; Socio-economic challenges.